Peran Pembelajaran Regulasi Diri dalam Menumbuhkan Motivasi Belajar Anak Usia 5-6 Tahun - Fika Septiana Sari (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2016)
Problems could hamper the child to achieve the goals or ideals. One of these problems was due to low motivation to learn children. Motivation could affect a person to perform a certain activity. Activities would be meaningful and successful if a child was motivated to learn. One alternative to foster motivation to learn was by self-regulated learning. The purpose of writing this article was to examine the role of self-regulation learning in the motivation to learn, especially for children aged 5-6 years. The method of writing this article was through the study of literature by searching several sources of literature relevant to the purpose of writing the article. From several literature were synthesized to see the relationship between learning motivation and self-regulation learning. The results of these discussions show that self-regulation learning with a learning technique that emphasized self-reliance and responsibility of children to regulate their own learning process that include analysis of tasks, planning, setting strategy, and reflection. Through self-regulation, the encouragement contained in the child both intrinsic and extrinsic motivation would be stronger so that it could assist in realizing the goal achievement in learning activities. Learning self-regulation could also transform the mental abilities of children aged 5-6 to be able to learn independently.